322 Prevalence of hrHPV DNA and p16/ki67 expression among women with cervical dysplasia. (13th November 2020) - ; Sekar, A; Nachiappa, R; Dhodapkar, R
Abstract : Objectives: Markers such as HPV DNA, p16 and ki67 are helpful to decide who among the screen positives require further management and treatment. So, this study was planned to estimate the prevalence of HPV DNA, p16 and Ki67 expression among the women with cervical dysplasia and to correlate high risk HPV DNA positivity and P16/Ki67 expression among them. Methods: In this hospital-based cross-sectional study, 146 women with abnormal Pap smear reports were included in the study and were subjected to HPV DNA testing and colposcopy and directed biopsy for histopathology and immuno-histochemistry for p16 and ki67. Women who have already received treatment for dysplasia and women who were pregnant were excluded from the study. Results: Totally 146 women with abnormal Pap report with a mean age of 47.8 years were studied. The prevalence of high-risk HPV was 44.5% and HPV 16, 56 and 18 were the common genotypes. The prevalence of P16 and Ki67 expression more than 5% was 20.5% and 34.3% respectively. Positive correlation was noted between high risk HPV and P16/Ki67 expression (p value of 0.0189 for P16 expression and HPV positivity, p value of 0.0027 for Ki67 expression and HPV positivity). Conclusions: The prevalence of high-risk HPV in our study population comprising of women with abnormal Pap smears was 44.5%. Positive correlation was noted between HPV, histopathology and P16 and Ki67 suggesting that these markers can be used as adjuncts in inconclusive cases during histopathological examination.